An Humanistic Mentoring Model in the Religious Transformation of Converts (Mualaf) in Pontianak - Nur Izzaturohmah; Helva Zurayah (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2026)
Existing literature has rarely addressed the implementation of humanistic mentoring for mualaf (recent converts to Islam) in fostering spiritual stability, social adaptation, and religious commitment within multicultural societies. The challenges faced by mualaf require religious guidance that not only enhances their understanding of Islamic teachings but also supports their adjustment to diverse social environments. As a multicultural city, Pontianak provides a significant context for examining the importance of sustainable and inclusive mentoring practices. Therefore, this study investigates the role of Yayasan Kejayaan Mualaf Indonesia (YKMI) in supporting the spiritual development and religious understanding of mualaf. This research employed a qualitative case study approach. Data were collected through observation, in-depth interviews, and document analysis and were analyzed inductively through coding, categorization, and interpretation. The findings indicate that YKMI implements a structured and continuous mentoring model through personal approaches, religious lectures, halaqah, consultation services, audio-visual media, dakwah materials, and silaturahmi activities. These mentoring practices contributed to improving mualaf’s religious literacy, understanding of worship, moral development, and spiritual and psychological well-being. Furthermore, the mentoring process encouraged positive changes in religious practice and fostered a more devoted, adaptive, and inclusive Islamic identity. This study highlights the importance of humanistic and sustainable religious mentoring in strengthening spiritual resilience and promoting social integration among mualaf within multicultural communities.